La política de las empresas en Latinoamérica: investigando sus estructuras, preferencias e influencia - Ross Schneider, Ben (2012)
The article surveys the study of Latin American business politics, focusing on three main areas: The structure of business, the preferences of business, and its power in the political process. The structure of businesses in Latin America is distinct, with a larger share of small and informal firms, comparatively small large firms, and a dominant​ role of multinational corporations (MNCs) and economic groups. We argue that these structures are reflected in business preferences. MNCs’ preferences depend on their strategic orientation, whether they invest in Latin America in order to gain access to resources, to new markets, or to enhance their global productivity. Business groups are often particularly strong in non-competitive industries – resources, oligopolistic non-tradables etc. - and are highly flexible due to hierarchical management and large cash reserves. As a result, they are well equipped to deal with a rapidly changing businesses environment and were, surprisingly to many observers, unlikely to oppose the external liberalization policies of the 1990s. Small firms have little political cloud, but since many of them are informal, they do not play an important part as a voice for flexibilization, especially of labor markets, the way they do in many advanced industrialized countries. Large firms have various avenues to influence political processes in Latin America. Business leaders are well represented in governments and are often included in advisory councils which can play crucial roles in affecting policy. The formal structure of political systems – Presidential systems with proportional representation in parliaments – further enhance the power of business, as individual legislators are often targeted for legislative deal-making. The region’s expensive political campaigns, funded by a small number of large donors, are yet another source for business power of the political process. Looking ahead, we argue that many of these features of Latin American businesses and business politics are likely to be quite stable and if anything increase in intensity. Keywords: Latin America; business politics; business power; economic groups; multinational corporations; small firms; literature review.